The price of freedom : slavery and manumission in Baltimore and early national Maryland - Whitman, T. Stephen, 1950- (University Press of Kentucky, 1997)
A stereotypical image of manumission is that of a benign plantation owner freeing his slaves on his deathbed. But as Stephen Whitman demonstrates, the truth was far more complex, especially in border states where manumission was much more common. Whitman analyzes the economic and social history of Baltimore to show how the vigorous growth of the city required the exploitation of rural slaves. To prevent them from escaping and to spur higher production, owners entered into arrangements with their slaves, promising eventual freedom in return for many years' hard work. The Price of Freedom revea.